2016
DOI: 10.1101/044446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptive divergence in transcriptome response to heat and acclimation inArabidopsis thalianaplants from contrasting climates

Abstract: Phenotypic variation in stress response has been widely observed within species. This variation is an adaptive response to local climates and is controlled by gene sequence variation and especially by variation in expression at the transcriptome level. Plants from contrasting climates are thus expected to have different patterns in gene expression. Acclimation, a pre-exposure to sub-lethal temperature before exposing to extreme high temperature, is an important adaptive mechanism of plant survival. We are inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…For example, a comparison of natural Chenopodium album biotypes from thermally variable environments showed that biotypes adapted to more stressful environments contained lower levels of certain Hsps than those from moderate habitats, both constitutively and in response to thermal stress. 99 Similar results were reported for Drosophila 100 and Arabidopsis, 101 suggesting that this is an evolutionarily conserved strategy for heat stress acclimation, proceeding through an as yet unknown mechanism. Our results indicate that a very different stress, i.e.…”
Section: Redox Maintenance/stress Responsesupporting
confidence: 67%
“…For example, a comparison of natural Chenopodium album biotypes from thermally variable environments showed that biotypes adapted to more stressful environments contained lower levels of certain Hsps than those from moderate habitats, both constitutively and in response to thermal stress. 99 Similar results were reported for Drosophila 100 and Arabidopsis, 101 suggesting that this is an evolutionarily conserved strategy for heat stress acclimation, proceeding through an as yet unknown mechanism. Our results indicate that a very different stress, i.e.…”
Section: Redox Maintenance/stress Responsesupporting
confidence: 67%
“…For example, a comparison of natural Chenopodium album biotypes showed that those adapted to stressful environments contained lower levels of certain HSPs than those from moderate habitats, both constitutively and in response to thermal stress . Comparable ecological studies of Drosophila and Arabidopsis reported similar findings, suggesting that this is an evolutionarily conserved strategy for stress acclimation. In a series of papers starting in 1998, it was proposed that HSP90 functions as a global regulator for stress adaptation by acting as a capacitor for phenotypic variation .…”
Section: Ntsr: a Role For Heat Shock Proteins?mentioning
confidence: 99%
“…], which is sensitive to high temperatures, shows a change in the metabolomics (Chebrolu et al 2016) and antioxidant production (Sgobba et al 2015). Heat waves can also affect plant growth, photosynthesis, and pollination quite drastically (Sakata et al 2014;Buchner et al 2015;Bishop et al 2016;Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%